Transforming Mathematics Teaching through GenAI: Classroom Experiences from Probability Lessons - Subedi, Sthir Babu; Shrestha, Shristi; Ghimire, Subekshya (Journal of Mathematics Education, 2026)
This study explores the use of Generative Artificial Intelligence (GenAI) tools, such as ChatGPT and Gemini, to teach probability to Grade 12 students in Nepal. Utilizing the Teaching Experimental Methodology (TEM), this study was conducted across three classroom sections, each comprising 38 to 42 students. Data were collected through interviews, classroom observations, reflective notes, and student assessment scores to examine students' engagement, conceptual understanding, learning experiences, and the teacher’s concerns regarding the integration of GenAI in the classroom. The findings indicated an increase in student engagement, characterized by active participation, peer discussions, and immediate feedback. Students demonstrated improved conceptual understanding by identifying errors in questions generated by AI and engaging in reflective problem-solving. Results also showed positive changes in metacognitive skills, and variations in learning experiences have been noticed. The study suggests that GenAI can support more interactive and student-centered mathematics instruction by adapting to students' needs, providing AI based teachers' trainings and careful verification of AI-generated contents.